Persian books of Munshi Naval Kishor’s publisher house which are stored in the National and Science Library of Kazakhstan (Journal of Oriental Studies, 2017)
This paper devoted to the Persian Printed books of well-known Indianpublisher Munshi Nawal Kishor (1836-1895) which were published inKanpur and Lakhnow. Most of the Persian Printed books were published inIndia, particularly in Munshi Nawal Kishor’s publisher house. Persian Printedbooks spread all over the India, even abroad India. Especially, manyPersian Printed books of Munshi Nawal Kishor’s publisher house wereused in maktabs and madrasas of Central Asia. Persian Printed books ofMunshi Nawal Kishor’s publisher house preserved in the fund of Nationaland Science Library of Kazakhstan considered as confirmation materials. Inthis paper Munshi Nawal Kishor considered as a person who contributed inthe development of education system of Central Asia with exact samples.